Paparan Timbal dan Stres Oksidatif: Dampak Klinis dan Mekanismenya - Rahmah Dara Ayunda; Ardiana Ekawanti; Fitriannisa Faradina Zubaidi; Khairil Pahmi; Arsy Muchlisa Putri; I Nyoman Rhino Raditya (Lombok Medical Journal, 2026)
Lead (Pb) exposure is a significant global environmental health concern, as this heavy metal lacks physiological function in the human body and is toxic, leading to various health disorders. One of the primary mechanisms of lead toxicity is the induction of oxidative stress, defined as an imbalance between the production of reactive oxygen species (ROS) and the capacity of endogenous antioxidant systems to neutralize them. Lead enhances ROS generation through mitochondrial dysfunction and reduces the activity of critical antioxidant enzymes, such as superoxide dismutase (SOD), glutathione peroxidase (GPx), and catalase (CAT), resulting in oxidative damage to lipids, proteins, and DNA, which subsequently triggers cellular and tissue dysfunction. The clinical consequences of lead-induced oxidative stress are observed across multiple organ systems, including the nervous system (cognitive impairment, memory loss, neuropathy), kidneys (nephropathy, decreased filtration function), liver (hepatotoxicity, metabolic disturbances), and the hematopoietic system (anemia, blood cell dysfunction). This literature review indicates that lead exposure induces cellular and tissue damage through multiple cellular pathways related to oxidative stress, elucidating the fundamental mechanisms by which lead causes clinical disorders in these organs. In conclusion, understanding these cellular mechanisms provides a scientific basis for linking lead exposure to the development of multi-organ diseases.